Liver specific overexpression of platelet-derived growth factor-B accelerates liver cancer development in chemically induced liver carcinogenesis - Maass, Thorsten; Thieringer, Florian R.; Mann, Amrit; Longerich, Thomas; Schirmacher, Peter; Strand, Dennis; Hansen, Torsten; Galle, Peter R.; Teufel, Andreas; Kanzler, Stephan (International journal of cancer, 2011)
A genetic basis of hepatocellular carcinoma (HCC) has been well-established and major signaling pathways, such as p53, Wnt-signaling, transforming growth factor-β (TGF-β) and Ras pathways, have been identified to be essential to HCC development. Lately, the family of platelet-derived growth factors (PDGFs) has shifted to the center of interest. We have reported on spontaneously developing liver fibrosis in PDGF-B transgenic mice. Since HCC rarely occurs in healthy liver, but dramatically increases at the cirrhosis stage of which liver fibrosis is a preliminary stage, we investigated liver cancer development in chemically induced liver carcinogenesis in these mice. HCC induction was performed by treatment of the mice with diethylnitrosamine and phenobarbital. At an age of 6 months, the tumor development of these animals was analyzed. Not only the development of dysplastic lesions in PDGF-B transgenic mice was significantly increased but also their malignant transformation to HCC. Furthermore, we were able to establish a key role of PDGF-B signaling at diverse stages of liver cancer development. Here, we show that development of liver fibrosis is likely through upregulation of TGF-β receptors by PDGF-B. Additionally, overexpression of PDGF-B also leads to an increased expression of β-catenin as well as vascular endothelial growth factor and platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31), all factors with established roles in carcinogenesis. We were able to extend the understanding of key genetic regulators in HCC development by PDGF-B and decode essential downstream signals.